Circadian variation affects the biology and digestive profiles of a nocturnal insect Spodoptera litura (Insecta: Lepidoptera). Issue 2 (4th March 2017) - Subala, Subramanian PanchuRavindraRajan; Shivakumar, Muthugounder Subramanian
Abstract: The present study was conducted to decipher the impact of circadian rhythm on digestive enzymes of Spodoptera litura under three photoperiods (12L:12D, 0L:24D, and 24L:0D). Longer life cycle, higher developmental traits and significant food utilizing capability were observed in dark conditions (DD), while there was no effect on survival. The activity of lactate dehydrogenase (LDH), α and β-glucosidase depended on complete absence of light (DD) while LL had a significant effect on protease activity. The presence of polypeptides (35, 60 kDa) and lower protease inhibition by PMSF in 0L:24D, and 24L:0D indicated that serine proteases (trypsin) were the main proteases in larval midgut. Overall, zymography profiles suggested that circadian variation, particularly dark period influenced the S. litura development due to fluctuations in the midgut enzymes via food utilization. Although the effect of photoperiod on digestive processes of insects is still unclear, dark regime may underlie the midgut digestive enzymes in S. litura larvae.